Maternal syphilis in a rural and urban community in Western Cape, South Africa: a cross-sectional analysis - De Araujo, Maxine (Department of Paediatrics and Child Health, 2025)
Background: Syphilis affects 2 million pregnant women globally each year, with 63% of cases occurring in sub-Saharan Africa. Untreated infection during pregnancy can lead to vertical transmission, resulting in congenital syphilis in 50–90% of cases. Global rates exceed the World Health Organisation's target for congenital syphilis of 50 cases per 100,000 live births, with many countries experiencing a resurgence in the past decade. South Africa's (SA) maternal syphilis prevalence rate increased from 2.6% in 2019 to 3.1% in 2022. While syphilis screening is mandated for all pregnant women in SA, the complexities of screening algorithms and result interpretation, as well as resource constraints, remain a challenge. Further research is required to understand the resurgence of maternal and congenital syphilis, evaluate the effectiveness of existing interventions and inform future actions. Aim: To describe maternal syphilis screening in terms of the implementation of the 2019 South African Prevention of Mother to Child Transmission (PMTCT) guidelines and prevalence in two communities, one urban and one rural, in the Western Cape (WC) province of South Africa. Methodology: This cross-sectional study was a secondary analysis of the longitudinal parent study, Children Human Immunodeficiency Virus (HIV) Exposed Uninfected - Research to Inform Survival and Health (CHERISH). Our study analysed data collected between January 2022 and June 2024 from pregnant women (24- and 36-weeks gestation) living with and without HIV (in at least a 1:1 ratio), enrolled from two communities in the WC province of SA; Gugulethu (urban) and the Breede Valley (rural). Demographic and clinical data were collected from Maternity Case Records and face-to-face interviews and syphilis laboratory results were retrieved from the National Health Laboratory Services TrakCare database. Data analyses were performed by descriptive statistics using STATA version 12,1 and statistical significance was determined using Chi-square or Fisher Exact tests using a significance level of 0.05. Results: Of 941 women, 600 were enrolled in Gugulethu and 341 in the Breede Valley. Most women were unemployed (67.3%), receiving government grants (57.2%), living in informal housing (57.2%), partnered with the father of the current pregnancy (83.5%), and attended their first antenatal care (ANC) visit in the second trimester (54.3%). Our study's HIV prevalence (57.6%) was affected by the enrollment of women with and without HIV in a ratio between 1:1 and 2:1. Our study found maternal syphilis prevalences of 5.0% (95% CI 3.5%-6.4%) for active infection and 5.8% (95% CI 4.3%-7.3%) for past infection, with significantly higher rates in the Breede Valley than in Gugulethu (6.4% [95% CI 3.8%-9.1%] and 7.6% [95% CI 4.8%-10.5%] versus 4.2% [95% CI 2.6%-5.8%] and 4.8%[95% CI 3.1%-6.6%], respectively, p = 0.00). Overall, 87.8% of women had point of care (POC) syphilis screening results recorded, with significantly higher screening rates in the Breede Valley (p = 0.00). However, only 74.3% of women with POC screening results were screened at the first ANC visit. Although 73.6% of women underwent Treponema Pallidum Hemagglutination Assay (TPHA) laboratory testing, 18.9% with reactive POC results did not receive follow-up laboratory testing. All women with reactive or equivocal TPHA laboratory results underwent Rapid Plasma Reagin (RPR) testing to confirm active infection, although unnecessary RPR testing was conducted at both research sites. Maternal syphilis status was significantly associated with socioeconomic status, relationship with the father of the pregnancy, parity, timing of ANC enrollment, HIV status, and pregnancy outcome. Prevalence rates of active (5.5%) and past (7.9%) syphilis were higher among women living with HIV than those without (4.3% and 3.0%, respectively). No significant associations were found with maternal age, gravidity, antiretroviral therapy in women living with HIV, prior obstetric complications, or hospitalisation during the current pregnancy. Conclusion: Although national and facility-level maternal syphilis screening guidelines were not optimally implemented at either research site, the Breede Valley's practices aligned more closely with the 2019 PMTCT guidelines. Suboptimal implementation included low screening rates at the first ANC visit, poor documentation of POC results, inadequate confirmatory testing for reactive POC results, and the misuse of laboratory resources. Both sites showed active maternal syphilis prevalence rates higher than reported figures, with the Breede Valley more affected. Active syphilis was associated with delayed ANC enrollment, while both active and past infections were more prevalent in women living with HIV and associated with higher stillbirth rates. However, our study was not powered to quantify significant relationships, and potential confounders were not accounted for. Strengthening monitoring, addressing non-compliance, and improving staff training are critical for improving maternal syphilis screening and reducing rising congenital syphilis cases.